El juego de rol como herramienta de desarrollo lógico matemático en niños de educación inicial de la unidad educativa “Carlos Cisneros”, ciudad de Riobamba, provincia de Chimborazo - Barahona Cuji, Clariza Socorro (2019)
The objective of the research was to determine the incidence of role plays in the mathematical logical development in the children of Initial Education of the Carlos Cisneros Educational Unit of the Riobamba Canton, Province of Chimborazo. The established methodology presents a mixed approach, that is, quali - quantitative, and is based on a descriptive scope. The study population was 34 infants (23 boys and 11 girls) between the ages of 4 and 5 years. In addition, a mathematical stimulation guide based on RPGs for children in early childhood education was applied. The test statistic, t-student, was used and the hypothesis was corroborated, stating a significant improvement in the mathematical logical development in the study group. The main results reflect that, 65% of the infants, reflect a deficit of knowledge about the contents treated in their educational level, in the same way, in the second data collection, there was a considerable increase of knowledge in the population of study. In conclusion, the mathematical activity from the perspective of the role play becomes a great methodological success by allowing to work together concepts, procedures and attitudes of infants Keywords: Roleplay, Mathematical Logical Development, Thought Development, Learning Process